Isolation and identification of duck egg-borne bacteria and their antibiogram profile - Ema, Fateha Akther; Arif, Mohammad; Islam, Md. Ariful; Khatun, Mst. Minara (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present study was aimed to isolate and identify the egg-borne bacteria from different parts of duck eggs such as egg shell (outer and inner), yolk and albumen, and to assess the anti-biogram profile of the isolated bacteria. Materials and methods: A total of 40 samples were collected randomly from different grocery shops of Bangladesh Agricultural University (BAU) Campus and Kaowatkhali, Mymensingh. Following necessary preparation, the samples were streaked onto various selective media like Salmonella-Shigella (SS) agar (for Salmonella spp.), Eosin Methylene Blue (EMB) (for E. coli), and Mannitol Salt (MS) agar (for Staphylococcus spp.) respectively for isolation of bacteria. The bacteria were confirmed based on cultural and biochemical characteristics. Antibiotic sensitivity test of the bacterial isolates was performed using seven antibiotics (Ampicillin, Chloramphenicol, Ciprofloxacin, Gentamicin, Vancomycin, Kanamycin and Cephalexin) by following disc diffusion method. Results: E. coli, Staphylococcus spp. and Salmonella spp. were isolated and identified from the duck egg samples. Prevalence of E coli in outer egg shell was 80%, whereas in inner egg shell and inner egg content, this prevalence was 20% and 10%, respectively. Similarly, the prevalence of Staphylococcus spp. was 75%, 17.5% and 7.5% in outer egg shell, inner egg shell and inner egg content, respectively. The prevalence of Salmonella spp. was 82.5% in outer egg shell, 22.5% in inner egg shell and 12.5% in inner content of egg. All these three bacterial isolates were sensitive to Ciprofloxacin and Gentamicin and resistant to Ampicillin and Cephalexin. Conclusion: The duck eggs harbor multi-drug resistant (MDR) bacteria which may impose public health hazards if these MDR bacteria are transferred to human through food chain. http://doi.org/10.5455/javar.2018.e253